Autofluorescence for the diagnosis of visceral pleural invasion in non-small-cell lung cancer. (8th December 2017) - Takizawa, Hiromitsu; Kondo, Kazuya; Kawakita, Naoya; Tsuboi, Mitsuhiro; Toba, Hiroaki; Kajiura, Koichiro; Kawakami, Yukikiyo; Sakiyama, Shoji; Tangoku, Akira; Morishita, Atsushi; Nakagawa, Yasushi; Hirose, Toshiyuki
Abstract: OBJECTIVES: This study was conducted to evaluate the accuracy of autofluorescence as a mode of diagnosis for visceral pleural invasion of non-small-cell lung cancer compared with white-light by means of clinical questions to several thoracic surgeons. METHODS: Eight independent thoracic surgeons evaluated visceral pleural invasion in 25 cases of non-small-cell lung cancer attached to the visceral pleura on lung windows of preoperative computed tomography images. At the first study meeting to evaluate the accuracy of visceral pleural invasion diagnosis using conventional white-light images, the surgeons diagnosed visceral pleural invasion based on information in preoperative computed tomography images, histological types and videos recorded with white-light mode using a thoracoscope. At the second study meeting to evaluate the accuracy of visceral pleural invasion diagnosis using autofluorescence, the same surgeons diagnosed visceral pleural invasion based on information in 2 videos recorded in white-light mode and in autofluorescence mode using the thoracoscope. RESULTS: The overall average sensitivity, specificity and accuracy of visceral pleural invasion diagnosis by white-light versus autofluorescence mode were 64.6% vs 83.3%, 53.9% vs 73.7% and 56.5% vs 76.0%, respectively. CONCLUSIONS: The sensitivity, specificity and accuracy of visceral pleural invasion diagnosis was improved through the additional use of the autofluorescence mode compared with the white-light mode alone.